Применение теории обнаружения для измерения поведенческих реакций животных - Солуха, Б.В. (Вестник зоологии, 1978)
Application of the methods based on the statistical theory of solutions to measure animals' reactions to the environment changes is promising in zoological researches. Measurements of zoological objects are distinguished by a specific set of components of generalized characteristics for detection of influences. The method for measuring characteristics of stimuli detection on the basis of the statistical detection theory is applied to study a wide class of behaviour and electrophysiological responses. Problems and a method of physical ethology follow from the theoretical and experimental developmenf of problems of measuring detection characteristics in zoological objects.